Sitagliptin Mitigates Total Body Irradiation-Induced Hematopoietic Injury in Mice. (25th July 2020) - Wang, Meifang; Dong, Yinping; Wu, Jing; Li, Hongyan; Zhang, Junling; Lu, Lu; Zhang, Yuanyang; Zhou, Zewei; Fan, Saijun; Li, Deguan; Meng, Aimin
Abstract : Sitagliptin, an inhibitor of the dipeptidyl peptidase IV (DPP4), has been implicated in the regulation of type 2 diabetes. However, the role and mechanism of sitagliptin administration in total body irradiation (TBI)- induced hematopoietic cells injury are unclear. In this study, we demonstrated that sitagliptin had therapeutic effects on hematopoietic damage, which protected mice from 7.5 Gy TBI-induced death, increased the numbers and colony formation ability of hematopoietic cells. These therapeutic effects might be attributed to the inhibition of NOX4-mediated oxidative stress in hematopoietic cells, and the alleviation of inflammation was also helpful. Therefore, sitagliptin has potential as an effective radiotherapeutic agent for ameliorating TBI-induced hematopoietic injury.